Geriatric head injuries: impact and outcomes - Nagocha, Vallabh B.; Yadav, Manish; Sharma, Divyam; Garg, Sunil (International Journal of Research in Medical Sciences, 2019)
Background: Elderly trauma patients present unique challenges and face more significant obstacles in recovery than their younger counterparts. They usually experience higher morbidity and mortality and slower recovery trajectories and have, on average, worse functional, cognitive, and psychosocial outcomes months or years post-injury than do younger patients. Methods: Authors conducted a study of elderly head injury patients to understand the epidemiology of geriatric TBI, the impact of comorbidities and management issues and outcomes in such patients. Authors had a total of 110 patients who presented with traumatic brain injury and were admitted in this hospital over 2 years. Authors also reviewed the literatures to study the factors affecting outcome after geriatric TBI and studied the role of aggressive neurosurgical management in geriatric TBI. Results: Among 68%(n=75) of the patients were male and 32% females. Age group of 60-65 years was the highest with 60.9% patients. Patients with GCS of 8 and below had the highest mortality rates of 68 %. Overall mortality rate was 32.72% and 9.09 % of the patients survived in a vegetative condition. The proportion of injury secondary to fall was the largest single group in 50.9% patients, and Chronic SDH was the most common pathology seen in 36.45 % patients. Highest mortality was seen in patients with Diffuse Axonal Injury (69.23 %). Out of the 110 patients , 57 patients underwent surgery for various pathologies. Chronic SDH were the most common operated pathology followed by acute SDH. Glassgow outcome scale was used as the measure of outcome in these series of patients. 32.72 % patients had a GOS score of 1 and 9.09 % had a score of 2. 18.18 % patients remained severely disabled with a score of 3 and nine patients (8.18 %) had a score of 4 and thirty five patients had good recovery (GOS-5). Conclusions: Due to the better treatment options there is an increase in the number of elderly around the world. Thus, the number of eldery individuals presenting with TBI to the emergency department is also on the rise more commonly due to falls than road traffic accidents. There is a need for specific prognostic and management guidelines for the elderly which can lead to better diagnosis, care and recovery and eventual short- and long-term outcomes in the elderly.